2020
DOI: 10.1186/s13068-020-01771-3
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the transmission efficiency of the noncyclic glyoxylate pathway for fumarate production in Escherichia coli

Abstract: Background Fumarate is a multifunctional dicarboxylic acid in the tricarboxylic acid cycle, but microbial engineering for fumarate production is limited by the transmission efficiency of its biosynthetic pathway. Results Here, pathway engineering was used to construct the noncyclic glyoxylate pathway for fumarate production. To improve the transmission efficiency of intermediate metabolites, pathway optimization was conducted by fluctuating gene expression levels to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…However, aceBA overexpression dramatically slowed cell gowth, which demonstrated the importance of flux balance between the GS and oxiditive TCA cycle (Li et al, 2014). Chen et al engineered E. coli for fumarate production via the glyoxylate pathway (Chen et al, 2020). They explored the effect of pyruvate carboxylase (pyc), citrate synthase (gltA), aconitase (acnB), isocitrate lyase (aceA), and succinate dehydrogenase (sdh) overexpression on fumarate production, and found that pyruvate carboxylase and isocitrate lyase played crucial roles.…”
Section: Production Of Fumarate and Malatementioning
confidence: 99%
“…However, aceBA overexpression dramatically slowed cell gowth, which demonstrated the importance of flux balance between the GS and oxiditive TCA cycle (Li et al, 2014). Chen et al engineered E. coli for fumarate production via the glyoxylate pathway (Chen et al, 2020). They explored the effect of pyruvate carboxylase (pyc), citrate synthase (gltA), aconitase (acnB), isocitrate lyase (aceA), and succinate dehydrogenase (sdh) overexpression on fumarate production, and found that pyruvate carboxylase and isocitrate lyase played crucial roles.…”
Section: Production Of Fumarate and Malatementioning
confidence: 99%
“…Plasmids pCas (Addgene #62225) and pTargetF (Addgene #62226) were gifts from Dr. Jiang Yu (Shanghai Institutes for Biological Sciences). Plasmids for expressing the L1 proteins of various HPV types (6,11,16,18,31,33,45,52,58) were previously constructed and described elsewhere [31].…”
Section: Strains Plasmids and Culture Conditionsmentioning
confidence: 99%
“…Indeed, this is a routine approach for the over-expression of recombinant proteins in eukaryotic cell systems, such as the CHO system for antibody production [16]. Many loci on the E. coli chromosome are appropriate insertion sites for exogenous genes, and several recombinant E. coli strains have been constructed for the production of valuable bio-products via the establishment of novel synthesis pathways [17][18][19]. Previous research suggests that there are three main factors to consider when constructing a chromosomally integrated expression strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The branching of the oxidative TCA cycle and GS occurs at the isocitrate level, and thus, the decreased activity of 2-ketoglutarate dehydrogenase does not affect the efficiency of succinic acid synthesis through GS reactions. The activation of the glyoxylate shunt in E. coli is generally achieved via inactivation of the transcriptional regulator IclR, which represses the expression of the aceBAK operon genes encoding GS enzymes, while the deletion of fumarase isozyme fumB and fumAC genes prevents fumaric to malic acid conversion [ [10] , [11] , [12] , 14 ]. The approaches aimed at further optimisation of fumaric acid production by the engineered strains include the following: 1) the inactivation of certain pathways of mixed-acid fermentation competitively consuming pyruvate and acetyl-CoA, the key precursor in target product biosynthesis, by the deletion of ldhA and ackA genes [ 10 , 11 , 14 ]; and 2) the increase in intracellular availability of phosphoenolpyruvate (PEP) for carboxylation through the modification of the glucose transport and phosphorylation system with the concomitant intensification of oxaloacetate (OAA) formation upon the overexpression of PEP-carboxylating phosphoenolpyruvate carboxylase, Ppc [ 10 –- 12 ].…”
Section: Introductionmentioning
confidence: 99%